Analysis of History Textbooks: A Review of Michel Foucault's Power Relations Theory - Ruslan, Ahmad; ., Sariyatun; ., Susanto (KnE Social Sciences, 2024)
History is known as a branch of science that studies human life in the past with its different dynamics and developments. The role of history in school is to provide students with an understanding of the ways of thinking and the processes involved in studying past events, and what is no less important to internalize national identity. Another form of historical writing in formal education is textbooks. Textbooks as one of the learning tools used in school must present historical facts that are truly objective and not only contain the interests of the government. The purpose of learning history is to evoke historical awareness in students so that they know their identity. Students must know their national identity as a whole, free from doctrines that contain political tendencies and must be taught to liberate their minds more broadly and liberate themselves to the complex and comprehensive construction of historical knowledge. Keywords: textbook, power relations, history learning, Michel Foucault